Dakwah Kultural Muhammadiyah antara Pembaruan dan Pembauran - Suparto, Suparto (el Harakah: Jurnal Budaya Islam, 2009)
Muhammadiyah has long been recognized as a movement of dakwah (Islamic promulgation), tajdid (religious renewal), and social empowerment, and has been recorded by the history as the point of departure toward the resurrection of Muslim community in Indonesia.  A dakwah activity with a social touch through educational efforts and social services has made this organization as an icon of a distinct Islamic modernization. Due to the increasing challenges faced by the dakwah activity, Muhammadiyah has to dovetail its movement with the sensitivity of cultural rooms located in the heart of Indonesian communities. Therefore, in this modern juncture, Muhammadiyah cannot be conceived as a movement without cultural sensitivity; a movement that tends to banish local cultural elements. This necessitates Muhammadiyah to acknowledge a spotlight where cultures have been well flourishing in such a colorful country. Muhammadiyah sudah lama dikenal sebagai gerakan dakwah, tajdid, pembaharuan sosial, dan telah dicatat sejarah sebagai titik tolak kebangkitan umat Islam di Indonesia. Aktivitas dakwah dengan sentuhan sosial melalui upaya pendidikan dan pelayanan sosial membuat organisasi ini sebagai ikon modernisasi Islam yang berbeda. Karena meningkatnya tantangan yang dihadapi dalam kegiatan dakwah, Muhammadiyah harus menyesuaikan gerakannya dengan kepekaan ruang budaya yang berada di jantung masyarakat Indonesia. Oleh karena itu, dalam era modern ini, Muhammadiyah tidak dapat dipahami sebagai sebuah gerakan tanpa kepekaan budaya; sebuah gerakan yang cenderung menghalau unsur-unsur budaya lokal. Ini mengharuskan Muhammadiyah untuk mengakui sorotan di mana budaya telah berkembang dengan baik di negara yang penuh warna.